Predictors of hepatatis B prevention and awareness among barbers in Gwer West Local Government area, Benue state, Nigeria - Gabriel, Ogbeyi Ofikwu; Joseph, Jenewari Atiye; Francis, Ogbeyi Aba; Tolulope, Afolaranmi O.; Paul, Aba John; Emmanuel, Ikpom Terhemba (International Journal of Research in Medical Sciences, 2021)
Background: The rapid increase in the prevalence of hepatitis B virus infection is an important public health issue worldwide. Millions of the general population is at an increased risk of being infected but they lack the awareness and preventive measures against this infection. This study was carried out among barbers in Naka, Gwer West Local Government area of Benue state, to determine the predictors of awareness and preventive measures against hepatitis B. Methods: A cross sectional descriptive study involving all barbers in Naka were carried out. Structured interviewer administered questionnaires were used in collecting data from the respondents. Data were analyzed using statistical Package for Social Science (SPSS) version 23.0. Adjusted odds ratio and 95% confidence interval were used as point and interval estimates on the logistic model while a p value of ≤0.05 was considered statistically significant. Results: The total number of respondents in this study was 57. The mean age of the respondents was 25.9±2.10. Majority (92.2%) of the respondents had heard of hepatitis B, 48.9% were able to identify the cause of the disease as virus. Majority of the respondents (78.7%) identified vaccination as a preventive measure against hepatitis B. On vaccination, more than half (51.1%) had been vaccinated against hepatitis B. Vaccination and information significantly affect prevention and awareness p=0.015 and 0.001 respectively. Conclusions: Awareness of hepatitis B was high in this study but awareness about causes and clinical presentations were low. There is need for proper health education programmes to improve their knowledge about hepatitis B and its prevention.